PENGARUH PENGUASAAN KONSEP TEOREMA LIMIT TERHADAP KEMAMPUAN MENYELESAIKAN SOAL-SOAL BARISAN DAN DERET PADA MAHASISWA - Haritsah Hammamah Herahap; Yuni Rhamayanti; Yeni Cholida (JURNAL CERMATIKA, 2022)
The background of this research is that the ability of students of the Mathematics Department of UGN Padangsidimpuan in solving problems in the Complex Analysis course, especially on the material of Rows and Complex Series, has not been satisfactory. This is because students are less able to master the concept of the Limit Theorem. Mastery of the concept of the Limit Theorem is one of the factors that affect students' ability to solve complex Rows and Series problems so that they can obtain satisfactory results. This type of research uses quantitative methods with an ex fost facto approach. The population of this study were 102 students of the Mathematics Department of UGN Padangsidimpuan, while the sample was 38 students. Sampling was done by simple random sampling technique. The instrument used as data collection is a test. The analyzed data were obtained in two stages. The first stage is descriptive statistical analysis stage and the second stage is inferential statistical analysis. Based on this, this study aims to determine the significant influence between mastery of the concept of the Limit Theorem on the ability to solve problems of sequences and series in students. The results obtained in this study indicate that there is a significant effect between the X variable and the Y variable. This is evidenced by the calculation of the T test, with the results Tcount > T table or 55.84 > 4.11.